The genetic basis for the biosynthesis of the pharmaceutically important class of epoxyketone proteasome inhibitors - Schorn, Michelle (2013)
The epoxyketone proteasome inhibitors are an established class of therapeutic agents for the treatment of cancer. Their unique α′,β′-epoxyketone pharmacophore allows binding to the catalytic β-subunits of the proteasome with extraordinary specificity. Here we report the characterization of the first gene clusters for the biosynthesis of natural peptidyl-epoxyketones. The clusters for epoxomicin, the lead compound for the anti-cancer drug Kyprolis(™), and for eponemycin were identified in the actinobacterial producer strains ATCC 53904 and Streptomyces hygroscopicus ATCC 53709, respectively, using a modified protocol for Ion Torrent PGM genome sequencing. Both gene clusters code for a hybrid non-ribosomal peptide synthetase/polyketide synthase multifunctional enzyme complex and homologous redox enzymes. Epoxomicin and eponemycin were heterologously produced in Streptomyces albus J1046 via whole pathway expression. Moreover, we employed mass spectral molecular networking for a new comparative metabolomics approach in a heterologous system and discovered a number of putative epoxyketone derivatives. With this study we have definitively linked epoxyketone proteasome inhibitors and their biosynthesis genes for the first time in any organism, which will now allow for their detailed biochemical investigation.